EVALUASI EFEKTIFITAS PROGRAM KELUARGA BERENCANA - Zuwono Putri E.01108074, Dwi Grestina (FISIP Universitas Tanjungpura, 2013)
This article means to assess how far the extent of the Family Planning Program in district Roban ofCentral Singkawang City has reached the target and to determine the extent of the family planning program hasbeen running, whether it has reached the goal. Issues raised are many people and fertile age couples who havenot used/ run family planning program. In this article, in-depth interviews conducted with the informant is 4Head of Women's Empowerment and Family Planning, Family Planning Division Chief, Division Head ofFamily Welfare and Health Department Singkawang. The result is a program of Family Planning In Singkawangare effective, in a sense has achieved its intended purpose, but there are still some obstacles in itsimplementation, especially in terms of human resources, and facilities owned. To that end, the government isrunning the family planning program in order to recruit workers/ family planning field workers and increase thefacilities and infrastructure in order to support the activities of the program.Â Keywords: Family Planning Program; Fertile Age couples; Family Welfare; Evaluate Effectiveness,Infrastructure.